2013
DOI: 10.1016/j.otsr.2013.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Reduction plasty for hypertrophic anterior cruciate ligament mucoid degeneration: Clinical and knee laxity outcomes in 23 cases

Abstract: Level IV. Retrospective study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 15 publications
1
33
0
Order By: Relevance
“…4,22 In the present series, the postoperative outcomes demonstrate that partial ACL debridement (radio frequency debulking) for MD-ACL can lead to complete resolution of symptoms, full range of movement, and improvement in quality of life. Morice et al demonstrated that in a 23 patients series who all underwent partial ACL debridement, 20% resulted in an unstable knee, 6 which was similar to that of our study. Patients should be made aware that this is a complication of the surgery and that it is related to the amount of ACL tissue that is debrided.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…4,22 In the present series, the postoperative outcomes demonstrate that partial ACL debridement (radio frequency debulking) for MD-ACL can lead to complete resolution of symptoms, full range of movement, and improvement in quality of life. Morice et al demonstrated that in a 23 patients series who all underwent partial ACL debridement, 20% resulted in an unstable knee, 6 which was similar to that of our study. Patients should be made aware that this is a complication of the surgery and that it is related to the amount of ACL tissue that is debrided.…”
Section: Discussionsupporting
confidence: 91%
“…However, due to limited recognition, study numbers are small and the optimum management strategy is yet to be elucidated. 5,6 This case series presents 31 cases of MD-ACL, characterizing the clinical presentation, examination findings, and radiological features. It is the first report within the literature that describes the natural history and compares this to arthroscopic ACL debridement using validated knee scores.…”
mentioning
confidence: 99%
“…A maximum pressure load of 250 N was used in the clinical study of ACL tears and 200 N of pressure load was considered to be the threshold necessary to obtain good reproducibility of measurements in injured knees [6]. Di Iorio et al [8], Lorbach et al [9], and Morice et al [10] applied a maximum pressure load of 134 N while Vauhnik et al [11,12], Beldame et al [13], Jenny and Arndt [14] and Pierrat et al [15] applied a maximum pressure load of 250 N.…”
Section: Introductionmentioning
confidence: 99%
“…Mucoid degeneration of anterior cruciate ligament (ACL) is a benign knee pathology with a frequency of 1.8% to 5.3% [1] [2]. Mucoid degeneration of ACL is well documented, but very little information exists about this clinical entity.…”
Section: Introductionmentioning
confidence: 99%